Abemaciclib and Vacuolin-1 induce vacuole-like autolysosome formation – A new tool to study autophagosome-lysosome fusion - Tanaka, Yoshinori; Hino, Hirotsugu; Takeya, Kosuke; Eto, Masumi (Biochemical and biophysical research communications, 2022)
Macroautophagy (hereafter autophagy) is a conserved cellular degradation system, impairments in which have been implicated in the development of a wide range of diseases, including cancer and neurodegenerative diseases. Autophagy is mainly comprised of two processes: the formation of autophagosomes and autolysosomes. A detailed understanding of the formation of autophagosomes has been obtained in the past several decades. However, limited information is currently available on the formation of autolysosomes, which may partially be attributed to fewer methods to study the formation of autolysosomes than that of autophagosomes. Abemaciclib (Abe) and vacuolin-1 (Vac) are drugs that suppress the progression of breast cancer and induce characteristic vacuole formation in cells. Since Abe-induced vacuoles have the appearance of autolysosomes, they may be used to examine the formation of autolysosomes. However, it remains unknown whether Abe-/Vac-induced vacuoles are regulated by autophagosome-lysosome fusion. Markers for endosomes, lysosomes, and autophagosomes (Rab7, LAMP1, and mRFP-GFP-LC3, respectively) indicated that Abe-/Vac-induced vacuoles were autolysosomes. Abe and Vac failed to induce vacuolation in ATG16L1-deficient autophagy-null cells. Furthermore, Abe-/Vac-induced vacuolation was suppressed by bafilomycin A1, an inhibitor of autophagosome-lysosome fusion, whereas it was facilitated by rapamycin and the overexpression of Beclin-1, inducers of autophagosome-lysosome fusion. Moreover, vacuole formation was inhibited by the knockdown of progranulin (PGRN), a regulator of autophagosome-lysosome fusion, and promoted by its overexpression. The present results suggest the potential of Abe-/Vac-induced vacuole-like autolysosomes as a tool for evaluating autophagosome-lysosome fusion and examining the effects of PGRN in autophagy. •Abe and Vac induce vacuole-like autolysosome formation.•Abe-/Vac-induced vacuole formation depends on autophagy.•Suppressor and inducer for autolysosome formation modulate the vacuole formation.•PGRN is required for Abe-/Vac-induced vacuole formation.